2012
DOI: 10.1111/j.1742-9536.2011.00033.x
|View full text |Cite
|
Sign up to set email alerts
|

Perceived acceptability of anorexia and bulimia in women with and without eating disorder symptoms

Abstract: Perceptions of the acceptability of eating-disordered behaviour were examined in young adult women with (n = 44) and without (n = 268) eating disorder symptoms. All participants viewed vignettes of anorexia nervosa (AN) and bulimia nervosa (BN) and responded to the same series of questions-addressing different possible ways in which the conditions described might be seen to be acceptable-in relation to each vignette. Participants with eating disorder symptoms perceived eating-disordered behaviour to be more ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 31 publications
0
6
1
Order By: Relevance
“…Given the methods of recruitment employed, it was not possible to determine response rates and no information was available concerning the characteristics of nonrespondents. However, comparison of participants' scores on the eating disorder symptom measure with those of normative data suggested that levels of eating disorder psychopathology in the present study sample were somewhat higher than those of young women in the general population, as would be expected (Luce et al, 2008;Mond & Arrighi, 2012;Mond, Hay, Rodgers, & Owen, 2006c).…”
Section: Downloaded By [University Of Reading] At 09:58 03 January 2015contrasting
confidence: 55%
See 3 more Smart Citations
“…Given the methods of recruitment employed, it was not possible to determine response rates and no information was available concerning the characteristics of nonrespondents. However, comparison of participants' scores on the eating disorder symptom measure with those of normative data suggested that levels of eating disorder psychopathology in the present study sample were somewhat higher than those of young women in the general population, as would be expected (Luce et al, 2008;Mond & Arrighi, 2012;Mond, Hay, Rodgers, & Owen, 2006c).…”
Section: Downloaded By [University Of Reading] At 09:58 03 January 2015contrasting
confidence: 55%
“…Third, probable eating disorder cases were identified on the basis of self-report assessment. Although interview assessment would have been preferable, participants identified as probable eating disorder cases in the present study had very high levels of eating disorder and comorbid psychopathology and the criteria employed in identifying these participants have been validated in several previous, community-based studies (Mond et al, 2007b(Mond et al, , 2009bMond & Arrighi, 2012). Fourth, the current study research, like that of Mond et al (2006b), included only female participants.…”
Section: Study Limitations and Other Methodological Considerationsmentioning
confidence: 94%
See 2 more Smart Citations
“…To achieve these "ideal," yet often unrealistic, appearances, individuals often alter their eating behaviors. This can contribute to the development of eating disorders, such as bulimia and anorexia nervosa (Mond & Arrighi, 2012). Thus, it is not surprising that dieting is strongly linked to the essence of femininity in the contemporary era (Meyer, Blissett, & Oldfield, 2001).…”
Section: Mediamentioning
confidence: 99%